Bank opacity and financial crises - Jungherr, Joachim (Journal of Banking & Finance, 2018)
This paper studies a model of endogenous bank opacity. Why do banks choose to hide their risk exposure from the public? And should policy makers force banks to be more transparent? In the model, bank opacity is costly because it encourages banks to take on too much risk. But opacity also reduces the incidence of bank runs (for a given level of risk taking). Banks choose to be inefficiently opaque if the composition of their asset holdings is proprietary information. In this case, policy makers can improve upon the market outcome by imposing public disclosure requirements (such as Pillar Three of Basel II). However, full transparency maximizes neither efficiency nor stability. The model can explain why empirically a higher degree of bank competition leads to increased transparency.